Alkoholowy "homo necros". Lektura "Nocnych zwierząt" Patrycji Pustkowiak - Szymańska-Dańczyszyn, Aleksandra (Zagadnienia Rodzajów Literackich, 2025)
This article offers a reading of Patrycja Pustkowiak’s novel Night Animals through the lenses of necroperformance and the ontology of the dead body. The protagonist, Tamara Mortus, is interpreted as a literary embodiment of homo necros — a subject suspended between life and death, whose addicted, fragmented body performs resistance against patriarchal and socio-cultural norms. Drawing on the theoretical frameworks of Ewa Domańska, Dorota Sajewska, and Wiktoria Krzywonos, the author situates female alcoholism within a discourse traditionally reserved for anorexia and war trauma, proposing an expanded conceptualization of homo necroperformance. By merging literary analysis with critical theory, this article demonstrates how Night Animals articulates the marginalized experience of female alcoholism in contemporary Polish literature. It argues that Pustkowiak’s novel reclaims agency for its protagonist through the affective, corporeal, and symbolic language of decay, grotesque materiality, and the aesthetics of death. The paper positions the alcoholic female subject as a subversive figure of homo necros, challenging norms not through speech, but through the performative expression of corporeal degradation.